DOES EMOTION MEDIATE THE EFFECT OF ETHICAL AWARENESS AND PERCEIVED SERIOUSNESS OF WRONGDOING ON THE PEER REPORTING INTENTION? - Dhiannisa Wahyu Putri; Andrey Hasiholan Pulungan; Meiliyah Ariani (ZILLZELL MEDIA PRIMA, 2025)
Academic misconduct is a widespread issue that educational institutions encounter worldwide. The potential harm caused by academic misconduct encourages education-al institutions to attempt to prevent and eliminate it, for instance, through promoting peer reporting. This study investigates the role of emotions in mediating the relationship between ethical awareness and perceived seriousness of wrongdoing on the peer's intention to report academic misconduct. A survey was sent online to students at four universities in Indonesia and Hungary from December 2022 until February 2023. One hundred sixty-five responses were analyzed by using SMART PLS 4. Findings indicate that students who are ethically aware are likely to disclose academic misconduct committed by their friends (β = 0.443, p =.000). Emotional responses also influenced students’ ethical awareness to report academic misconduct (β = 0.269, p = 0.009). In contrast, our study found that students will not report academic mis-conduct, regardless of students' emotions despite the seriousness of wrongdoing (β = -0.046, p = 0.164). By acknowledging the impact of emotions on variable relation-ships, students can develop a better understanding of the cognitive and affective fac-tors involved in ethical decision-making. This understanding can then be leveraged by educational institutions to promote effective ways of fostering ethical behavior.